2008
DOI: 10.1016/j.drugalcdep.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of clinical trials for alcohol dependence to community samples

Abstract: There is a growing concern that results of tightly controlled clinical trials of individuals with alcohol use disorders may not generalize to broader community samples. To assess the proportion of community-dwelling adults with alcohol dependence who would have been eligible for a typical alcohol dependence treatment study, we developed a new, simple method: we applied a standard set of eligibility criteria commonly used in alcohol outcome studies to a large (n = 43,093) representative US adult sample intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 47 publications
4
58
0
Order By: Relevance
“…168 The samples in the randomized trials are different from community samples with AD; 169 but it is hard to predict what this means in terms of outcome. At this point, we can only indicate this potential bias in our estimations.…”
Section: Bimentioning
confidence: 99%
“…168 The samples in the randomized trials are different from community samples with AD; 169 but it is hard to predict what this means in terms of outcome. At this point, we can only indicate this potential bias in our estimations.…”
Section: Bimentioning
confidence: 99%
“…For alcohol dependence, which has been the most extensively studied, 79% of treatment-seeking individuals would be ineligible under at least one prevalent clinical trial criterion (Blanco et al, 2008). Other work has shown that African Americans are particularly likely to be underrepresented in alcohol-dependence trials (Humphreys, 2003;Humphreys and Weisner, 2000;Humphreys et al, 2007) and that, beginning in the 1970s, treatment outcome studies have become increasingly restrictive in their enrollment procedures (Humphreys et al, 2005).…”
mentioning
confidence: 99%
“…For example, in one large study, 75.8% of patients with major depression in the community would have been excluded from a typical RCT. 25 Treatment with sildenafil was well tolerated in the clinical practice population studied in the present observational analysis. No serious treatment-related cardiovascular events were reported.…”
Section: Sildenafil For Erectile Dysfunction In the Middle Eastmentioning
confidence: 96%